The Distribution of Skull Score and Skull Density Ratio in Tremor Patients for MR-Guided Focused Ultrasound Thalamotomy - Tsai, Kevin Wen-Kai; Chen, Jui-Cheng; Lai, Hui-Chin; Chang, Wei-Chieh; Taira, Takaomi; Chang, Jin Woo; Wei, Cheng-Yu (Frontiers in Neuroscience, 2021)
Objective MR-guided focused ultrasound (MRgFUS) is a minimum-invasive surgical approach to non-incisionally cause the thermos-coagulation inside the human brain. The skull score (SS) has already been approved as one of the most dominant factors related to a successful MRgFUS treatment. In this study, we first reveal the SS distribution of the tremor patients, and correlate the SS with the image feature from customized skull density ratio (cSDR). This correlation might give a direction to the future clinical study for improving the SS. Methods Two hundred and forty-six patients received a CT scan to the brain, and a bone-enhanced filter was applied and reconstructed to a high spatial resolution CT images. The SS of all patients would be estimated by the MRgFUS system after importing the reconstructed CT images into the MRgFUS system. The histogram and the cumulative distribution of the SS from all the patients was calculated to show the percentage of the patients whose SS lower than the 0.3 and 0.4. The same CT images of all patients was utilized to calculated the cSDR by first segmented the trabecular bone and the cortical bone from the CT images and divided the averaged trabecular bone intensity (aTBI) by the averaged cortical bone intensity (aCBI). The Pearson’s correlation (R) between the SS and the cSDR, aTBI, and the aCBI were calculated respectively. Results There were 19.19% and 50% of the patient who had the SS lower than the empirical threshold 0.3 and 0.4 respectively. The Pearson’s correlation between the SS and the cSDR, aCBI, and the aTBI were R = 0.8145, 0.5723 and 0.8842. Conclusions There were only half of the patients was eligible for the MRgFUS thalamotomy based on the SS, and near 20% of the patients were empirically difficult to achieve a therapeutic temperature during MRgFUS. The SS and our cSDR are highly correlated, and the SS had higher correlation with aTBI than that with aCBI. This is the first report to explicitly reveal the SS population and indicate a potential way to increase the chance to achieve a therapeutic temperature for those who originally has low SS.